Seasonal Constellation of Juvenile Whale Sharks in Gorontalo Bay Coastal Park - Yasir, Moh.; Hartati, Retno; Indrayanti, Elis; Amar, Fahri; Tarigan, Ariyo Imanuel (Marine Science Department Diponegoro University, 2024)
The whale shark (Rhincodon typus Smith, 1828) is the largest extant fish species in the world, and it is endangered, with population numbers declining in the last three decades. The appearance of whale sharks in the Botubarani Waters has attracted a lot of attention. Therefore, this study aimed to determine the whale shark's appearance, their habitat constellation pattern, and its oceanographic conditions. This research was conducted during the 2019-2022 period. The Photographic Identification (Photo-ID) method is used to observe and determine whale shark individual's number and pattern of presence. Oceanographic data includes chlorophyll-a concentration using Ocean Color Image (CCI) data and sea surface temperature (SST) using OSTIA image data processed with Interactive Data Language (IDL) software. The research showed there are 38 individuals with an estimated total length ranging from 2.3 to 7.3 meters. All whale sharks appearing in Botubarani include juvenile male individuals with a composition of 53% new individuals (N=20) and 47% (N=18) old individuals seen again with a rare seasonal and sporadic presence pattern mainly in the Eastern season (June). The average SST value during the study period ranged from 28.36-30.29⁰C while chlorophyll-a ranged from 0.174-0.698 mg.m-3. Although the present findings show that the whale shark's appearance in Botubarani waters was not significantly influenced by SST and chlorophyll-a, it might be affected by other oceanography factors such as Sea Surface Height Distribution (SSHD) and depth (Bathymetry). As the Botubarani aggregation site is the only whale shark emergence area with easy access throughout the year and is rapidly developing into a new ecotourism industry in Indonesia; the information on whale shark appearance provides useful support for the sustainable protection and Whale Sharks conservation in the future.